MCTP2 is a novel biomarker promoting tumor progression and nodal metastasis in oral squamous cell carcinoma - Yudai Shimojukkoku; Ayami Tomishima; Takayuki Ishida; Yuka Kajiya; Yasunobu Oku; Koshiro Kawaguchi; Takahiro Tsuchiyama; Kaori Shima; Hideto Saijo; Tomonori Sasahira (Scientific Reports)
Abstract Head and neck cancer is the sixth most common cancer worldwide. Among them, oral squamous cell carcinoma (OSCC) has remarkable local invasiveness and lymph node metastasis and is frequently found at an advanced stage. The 5-year survival rate of OSCC has remained at approximately 50% for several decades, and there is an urgent need to identify molecular markers that are effective for early diagnosis and treatment. Multiple C2 transmembrane proteins (MCTPs) are C2 domain-containing proteins, with two subtypes in humans: MCTP1 and MCTP2. MCTP1 has been reported to exhibit tumor-promoting activity in several cancer types; however, the role of MCTP2 in cancer remains largely unknown. In this study, we performed a comprehensive analysis using big data from over 500 head and neck cancer cases registered in The Cancer Genome Atlas (TCGA), expression profiling of 63 OSCC samples, and in vitro functional assessment using cell lines to elucidate MCTP2 involvement in OSCC. Compared to normal oral mucosa, MCTP2 expression was elevated in OSCC, and its expression rate was significantly increased at both protein and mRNA levels in cases with lymph node metastasis. In vitro experiments using two OSCC cell lines demonstrated that MCTP2 may be involved in cancer cell migration, invasive capacity acquisition, and epithelial-mesenchymal transition (EMT) phenotype. Furthermore, MCTP2 expression levels were upregulated by TGF-β1 in a concentration-dependent manner. These findings suggest that MCTP2 may serve as a novel marker of invasion and EMT in OSCC, with promising implications for developing new MCTP2-targeted diagnostic and therapeutic approaches for OSCC.